Cloning and characterization of polyphenol oxidase cDNAs of Phytolacca americana. - Joy, R W (1995)
Two cDNA clones encoding polyphenol oxidases were isolated from a cDNA library constructed from a log-phase suspension culture of Phytolacca americana (pokeweed) producing betalains. The clones exhibit 93 and 86% sequence identity at the nucleotide and deduced amino acid levels, respectively. Both clones contain two copper-binding domains characterized by histidine-rich regions, which are found ubiquitously in all polyphenol oxidases/tyrosinases, and a putative third histidine-rich, copper-binding region, which is common to all plant polyphenol oxidases. One of the Phytolacca cDNA deduced amino acid sequences contains the ubiquitous transit peptide for all proteins targeted to the internal lumen of thylakoid membranes of plastids and is considered to be 98 residues in length based on a proposed sequence cleavage site motif. This would produce a processed peptide of approximately 54 kD. In addition to common features of transit peptides, it was found that an additional conserved region for polyphenol oxidases was located between the hydroxy amino acid-rich region and the thylakoid transfer domain. Spatial and temporal expression was investigated by northern blot analysis of total RNA from various organs of Phytolacca plants. Transcripts of the two clones were found to be 2.1 and 2.3 kb, respectively. Both transcripts were present only at substantial levels in ripening, betalain-containing fruit.